The total score of athleticism profiles among Malaysian football players: a binary logistic regression analysis - Rosetam Affandi, Muhammad Farizul Haiqal; Raja Azidin, Raja Mohammed Firhad; Abdul Rahim, Farhanah; Aiman, Suhana; Choo, Yee Yu; Aston, Ngai; Geik, Yong Ang (Faculty of Sports Science and Recreation, 2025)
Performance-based tests are commonly used by strength and conditioning coaches to assess athletes and the purpose can ranged from functional diagnostic to decision making in return-tosport. Although these individual tests provide precise information on the strengths and weaknesses of each athlete, the large amount of such data can complicate communication between various stakeholders. Therefore, the present study aims to investigate the utility of a composite score called total score of athleticisms (TSA) in Malaysian football players and to examine the predictive ability of the TSA to identify group membership. A total of ninety-five male Malaysian football players participated in this study and their performance in vertical jump, 30-m sprint and yoyo intermittent recovery level 2 were measured. The result of each performance test was converted to a standard score and averaged to create the TSA of each athlete. The results from independent t-test indicated significant differences of moderate to large effect sizes (Cohen’s d of 0.69 to 1.07) in age, height, body mass and TSA scores (p ≤ 0.001) between senior and developmental players. Logistic regression analysis showed that TSA score was able to distinguish between senior and developmental players (χ2 (1, n = 95) = 23.763, p < 0.001). The TSA score accounted for 29.5% of the variance in group membership and correctly classified 70.5% of the players. When TSA scores were divided into tertiles, the CochranArmitage analysis indicated a statistically significant trend in the number of senior players across tertiles (z = 19.432, p < 0.001) with the percentage of senior players being the highest (77.1%; 27/32) in the high TSA tertile followed by medium (40.6%; 13/32) and low (29.0%; 9/31) TSA tertiles. The ability of the TSA to differentiate between senior and developmental players could be attributed to power indicators being a significant predictor of successful performance among elite football players and hence, highlights its potential use by coaches to streamline collaborative communication and for team selection.